Potensi dan Dampak Kebijakan Wajib Spin-off terhadap Unit Usaha Syariah dalam Sektor Perbankan - Muhammad Riadi Setiawan; Dendi Marcello (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
Banks are financial institutions that play a very important role in the economy and continue to innovate by developing various new forms and services. Spin-offs of Sharia Business Units (UUS) are a new method in the world of Islamic banking with the aim of becoming independent Islamic banks in conducting business activities based on sharia principles. The spin-off of the SBU is one of the main focuses of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector. Furthermore, referring to the provisions in Financial Services Authority Regulation Number 12 of 2023 concerning Sharia Business Units, conventional banks can carry out banking activities in accordance with sharia principles by being required to open an SBU. This shows that the UUS is a unit that remains part of the conventional bank, and the provisions governing its activities, even though they are carried out by conventional banks, must still follow sharia principles, including prohibiting interest-based transactions. This study shows that spin-offs of UUS have great potential to drive the growth of Islamic banking. A spin-off is a company's decision to restructure, which has various legal implications. Although spin-offs of Islamic banks have the potential to improve the performance of Islamic banking, government policies that require spin-offs without considering the specific context of each bank can hinder the development of this sector. The implementation of mandatory spin-off policies needs to be balanced with more comprehensive government policy support.